PENGARUH PENGGUNAAN MEDIA FILM ANIMASI KARTUN TERHADAP KEMAMPUAN MENULIS KARANGAN NARASI SISWA KELAS IV SD NEGRI 25 PALEMBANG: - Intan Permata Sari; Nuranisa; Robert Budi Laksana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to address issues related to the teaching of Indonesian language, specifically in the subject of “Writing Narrative Essays” for fourth-grade students. The problem arises due to several factors, including the teacher relying solely on LKS (student worksheets) and textbooks as the only learning tools. This has led to a lack of student interest and boredom during Indonesian language lessons. Assessment results show that 49% of students did not reach the minimum mastery criteria (KKTP). Therefore, students need appropriate learning media.This research employs a quantitative method with a quasi-experimental design. There are two variables in this study: variable